2019
DOI: 10.1186/s41072-019-0042-9
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating ocean carrier selection criteria: perspectives of Tasmanian shippers

Abstract: The purpose of this paper is to evaluate the decision process of Tasmanian shippers when selecting an ocean carrier. Data collected through an internet-based survey is described, and influential selection criteria are reported with the use of exploratory factor analysis. The findings indicate that Tasmanian shippers are both price and service conscious. Tasmanian shippers, unlike their mainland Australian counterparts, have an overwhelming reliance on maritime transportation. The exploratory factor analysis in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…The deciding factors for involving freight forwarders or NVOCC are the shippers' experience level in handling project cargo, convenience, air and sea freight requirements integration to a 3PL provider, price, and services. The most crucial deciding factor to include NVOCC is the need for carriers to provide end-to-end logistics with time-sensitive leveraging their robust networking system to simplify the logistics process, especially for international projects (Fanam and Ackerly 2019).…”
Section: Project Logistics Riskmentioning
confidence: 99%
“…The deciding factors for involving freight forwarders or NVOCC are the shippers' experience level in handling project cargo, convenience, air and sea freight requirements integration to a 3PL provider, price, and services. The most crucial deciding factor to include NVOCC is the need for carriers to provide end-to-end logistics with time-sensitive leveraging their robust networking system to simplify the logistics process, especially for international projects (Fanam and Ackerly 2019).…”
Section: Project Logistics Riskmentioning
confidence: 99%
“…As carrier selection criteria are related to service performances determined through various analyses in a number of studies, it is considered that these criteria are among the dimensions of service quality (Thai, 2008). For the purpose of evaluating the decision-making process related to carrier selection in linear transportation Fanam & Ackerly (2019) identified the following five dimensions regarding the selection of liner transportation lines: "service fee, itinerary & freight network, door-to-door transport, corporate social responsibility" They concluded that the most important criteria explaining these dimensions are "the lowest possible freight rate, flexibility of freight rate, domestic and international service network, schedule reliability (ontime arrival and departure), schedule frequency, transit timeframe, perceived reputation of carrier, problem-solving capability"…”
Section: Dimensions Of Liner Maritime Transport On Service Qualitymentioning
confidence: 99%
“…While there are numerous studies on service quality in other sectors, very few research directly addresses the dimensions and criteria (determinants) of quality in liner maritime services. Such dimensions and criteria are discussed in studies emphasizing mode or carrier selection criteria (Ho et al 2017;Fanam & Ackerly 2019. On the other hand, the analysis and discussion of the selection variables based on groups of factors allows for identifying the service-and performance-related attributes that are considered to be within the scope of dimensions of service quality (Thai, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, enterprises with logistics outsourcing demand face the problem of how to determine the optimal carrier selection. Speaking generally, the decision criteria of carriers can be categorized into two types: cost and service [1] . Mohammaditabar and Teimoury [2] constructed an optimal carrier selection model that simultaneously achieves the objectives of maximizing total profit and minimizing inventory and delivery cost.…”
Section: Introductionmentioning
confidence: 99%